PENERAPAN REGRESI DATA PANEL PENGARUH KESETARAAN GENDER TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI RIAU PERIODE 2011-2015 - Sutri Vininda; Lia Yuliana (Seminar Nasional Official Statistics, 2020)
Economic growth is which one indicator to evaluate the economic performance of a region. During the 2011-2015 period, economic growth in Indonesia decline, where Sumatra Island had the lowest economic growth, especially in Riau Province. Economic growth is obtained from production factors owned by a region. The existence of gender differences can lead to differences in productivity between workers, so in assessing economic growth it is necessary to include gender equality in the economy. This study aims to describe in general economic growth and gender equality and to determine the impact of gender equality on economic growth in Riau Province during the 2011-2015 period using descriptive analysis and panel data regression. The results showed that conditions of gender equality in the field of technology and labor force had increased while conditions for gender equality in the field of education had decreased. The panel data regression results show that the ratio of accessing the internet, the ratio of working hours, and the ratio of wages have a significant positive effect on economic growth, while the MYS ratio has not significant positive effect on economic growth.